Meningkatkan Program Pemberdayaan Perempuan dan Keluarga Berencana - Zakiyuddin Zakiyuddin; Firzan Firzan; Yarmaliza Yarmaliza; Teungku Nih Farsini; Fitriani Fitriani; Fitrah Reynaldi; Maiza Duana; Sufyan Anwar (Asosiasi Dosen Akuntansi Indonesia, 2021)
Women in low socioeconomic societies are sometimes in a disadvantageous condition and even tend to be in a helpless position due to the lack of support from various parties. This helpless situation can be seen from the lack of opportunity in making a decision in his life including in making decisions relating to himself and the Family Planning program. This helplessness makes women in a marginal condition in the element of society. The lack of encouragement from women can also be seen in the participation of family planning programs. The decision to use contraception is more often determined by men. Even to become a family planning acceptor is also determined by other parties, especially men. Meanwhile, very few men are family planning acceptors. This phenomenon is due to the decision to become a KB acceptor in the hands of men, so there is reluctance if the men become KB acceptors. Family planning services are not only related to being a family planning acceptor, but also many programs relating to empowerment, especially women. Women's empowerment programs in family planning programs are related to empowerment activities which are subsequently linked to family life. The results with family planning programs are still few that can empower women. This consideration is due to the still strong dominance of men in the norms of everyday society.